Wheat streak mosaic virus resistance in eight wheat germplasm lines. Issue 1 (22nd December 2015) - Zhang, Xinzhong; Bai, Guihua; Xu, Rugen; Zhang, Guorong
Abstract: Wheat streak mosaic virus (WSMV) is a destructive pathogen in wheat ( Triticum aestivum L.). Host resistance is the most effective way to control this virus. To date, Wsm2 is the only wheat resistance gene that is genetically mapped. The objective of this study was to identify germplasm lines that might carry resistance genes different from Wsm2 . Eight newly reported resistant germplasm lines were examined by allelic tests. To validate the allelic test results, five of them were further analysed for the inheritance of WSMV resistance. A Wsm2 ‐linked marker was also genotyped on populations developed for the inheritance study. Our results suggested that the WSMV resistance in lines CItr9358, PI225288, PI243652, PI245439, PI245526 and PI478095 was controlled by either Wsm2 or a gene very closely linked to Wsm2 . The resistance in PI243753 and PI321730, however, is likely controlled by a gene different from, but linked to Wsm2 . The resistance in PI321730 might also involve some minor genes. This study provided useful information for breeders to select appropriate resistant lines to improve WSMV resistance in wheat.